علم النفس الرياضي - شراطي ، رشيد (Mohamed Boudiaf University of M'Sila, 2023)
الملخص بالعربية: يكتسي مقرر علم النفس الرياضي أهمية بالغة في المسار التعليمي والتكويني للطالب في ميدان علوم وتقنيات النشاطات البدنية والرياضية، بكل تخصصاته، وأن هذه الأهمية البالغة التي يحتلها هذا المقرر تتأت من الأهمية التي أضحت تحتلها الجوانب النفسية (الانفعالية والعقلية) في شخصية الرياضي بغض النظر عن نوع الرياضة التي يمارسها، خاصة في ظل تقارب مستوى الرياضيين في الجوانب البدنية والمهارية والخططية، وكذلك الرغبة الدائمة في تحقيق الإنجاز الرياضي والثبات عليه. ومن بين أهم المعارف التي لا بد أن يكتسبها الطالب في هذا الميدان، المعرفة والدراية بالجوانب النفسية (الانفعالية والعقلية) لمختلف الفاعلين في المجال الرياضي لا سيما الرياضي والالمام بطرق قياسها والكشف عنها وتنميتها وتطويرها وضمان استدامتها (التقييم والتقويم لهذه الجوانب النفسية). Searchlight in English The sports psychology course is of great importance in the educational and training path of students in the field of physical and sports activities and technologies, in all its specializations. The great importance of this course stems from the importance that psychological aspects (emotional and mental) in the personality of athletes, regardless of the type of sport they practice, especially given the similarity in the physical, technical and tactical abilities of athletes, as well as their constant desire to achieve and maintain sporting success. Among the most important knowledge that students must acquire in this field is knowledge and understanding of the psychological aspects (emotional and mental) of various actors in the field of sports, especially athletes, and familiarity with the methods of measuring, detecting, developing and ensuring the sustainability of these aspects (assessment and evaluation of these psychological aspects).
Keywords: علم النفس الرياضي; الجانب الانفعالي للرياضي; الجانب العقلي للرياضي; التدريب العقلي